Konstruksi Realitas Isu Papuan Lives Matter di Media Online - Oktaviani, Ni Luh Putu Murni; Alit Suryawati, I Gusti Agung; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium; Vol 1 No 2 (2021): Jurnal Ilmu Komunikasi 2021, 2021)
In mid-2020, a lively Papuan Lives Matter campaign appeared on social media Twitter. The Papuan Lives Matter campaign has emerged after a Black Lives Matter campaign demanded justice for George Floyd's death due to violent officers. The Papuan Lives Matter campaign is a campaign adopted by Black Lives Matter to voice racism experienced by Papuans. During this time, Papua was seen as experiencing racism as it did to black people in the United States. Papuan Lives Matter comes as a form of solidarity and a campaign against racism against Papuans. Papuan Lives Matter has also become widely discussed on social media and mass media. Many mass media outlets preach Papuan Lives Matter with different points of view, including in  Tempo.co  and Antaranews.com. This study used Zhongdang Pan &Gerald M. Kosicki's framing analysis of  Tempo.co  and  Antaranews.com  news to look at the construction of  Tempo.co  reality and   Antaranews.com  on Papuan Lives Matter. Keyword:   Framing Analysis Zhongdang Pan and Gerald M.Kosicki, Reality Construct, Racism, Papuan Lives Matter.